Rumah Pintar: Strategi Mengembangkan Kreatifitas Pada Anak Jalanan Usia Sekolah Dasar - Amrullah Mahmud; Khaerunnisa Taayibu; Hasbahuddin (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2022)
Through Smart Houses that can increase the creativity of street children, it will help improve the social functions of street children, because the creativity of street children will provide more value for street children. using several methods. The method used in the form of lectures, exercises, discussions, and practice. The result of this activity is the creation of the Andi Matappa Smart House. Smart home is a community house that has many functions. For children, a smart house can be a place for them to learn, especially for street children who may not be able to get a formal education, therefore this smart house is very useful for them.